Bioengineering of Microalgae: Recent Advances, Perspectives, and Regulatory Challenges for Industrial Application - Kumar, Gulshan; Shekh, Ajam; Jakhu, Sunaina; Sharma, Yogesh; Kapoor, Ritu; Sharma, Tilak Raj (Frontiers in Bioengineering and Biotechnology, 2020)
Microalgae, due to their complex metabolic capacity, are being continuously explored for nutraceuticals, pharmaceuticals and other industrially important bioactives. However, suboptimal yield and productivity of the bioactive of interest in local and robust wild-type strains are of perennial concerns for their industrial applications. To overcome such limitations, strain improvement through genetic engineering could play a decisive role. Though the advanced tools for genetic engineering have emerged at a greater pace, they still remains under-used for microalgae as compared to other microorganisms. Pertaining to this, we reviewed the progress made so far in the development of molecular tools and techniques, and their deployment for microalgae strain improvement through genetic engineering. The recent availability of genome sequences and other omics datasets form diverse microalgae species have remarkable potential to guide strategic momentum in microalgae strain improvement program. This review focuses on the recent and significant improvements in the omics resources, mutant libraries and high throughput screening methodologies helpful to augment research in the model and non-model microalgae. Authors have also summarized the case studies on genetically engineered microalgae, and highlight the opportunities and challenges that are emerging from the current progress in the application of genome-editing to facilitate microalgal strain improvement. Towards the end, the regulatory and biosafety issues in the use of genetically engineered microalgae in commercial applications are described.